PENGARUH SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT DAN SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS TERHADAP EFEKTIFITAS PENGENDALIAN PIUTANG: (Studi Kasus Pada PT Tera Data Indonesia) - Dwi Astuty Dharma Putri; Taufik Aziz (Jurnal Proaksi, 2017)
The purpose of this research is to find out and learn how much influence thesales accounting information system, the cash receipt accounting information system onthe effectiveness of controlling accounts receivable. The population in this study is limitedto PT Tera Data Indonesia's employees. The sampling technique was 30 respondents.Data collection techniques use primary and secondary data with the help of SPSS version20. For windows. From the test results it can be concluded that the credit salesaccounting information system, the cash receipt accounting information system has aneffect on the effectiveness of the accounts receivable control.Keyword : Credit Sales Accounting Information Systems, Accounting InformationSystems Cash Receipts, Accountability Control Effectiveness.